FINANCIAL CONDITION OF LOCAL GOVERNMENT AFTERMATH OF COVID 19 PANDEMIC-ARCHIVAL ANALYSIS - Ika Kurnia Indriani (Jurnal Aplikasi Akuntansi, 2023)
This research aims to examine two aspects: (1) the provincial government of Indonesia's financial condition index; and (2) the influence of the financial condition on cases of COVID 19 handling. This study uses a descriptive quantitative approach with archival data analysis for 2015-2021. The provinces of Aceh, DKI Jakarta, Kalimantan Timur, NTT, and Papua Barat have the best financial condition index in Indonesia, according to an assessment of provincial government financial health. Financial condition has an simultaneous effect on COVID-19 pandemic handling. The results showed that H1 was approved with sig. 0.001 of simultaneous influence of provincial government's financial condition on COVID-19 cases. H3 is recognized with sig <0.001 that financial independent index partial effect on COVID-19 cases. With a sig. 0.187, H3 is rejected, indicating that budget solvency has no partial impact on the 19 cases. With a sig. 0.885, H4 is refused, indicating that service level solvency has no influence on situations of COVID-19. Budget solvency, financial independence, and service level solvency are independent variables that can account for 38,1% of the 19 covid cases that occurred in the province.